Diseño preliminar del núcleo de un reactor compacto. - Canepa, Juan F. (Comisión Nacional de Energía Atómica. Instituto Balseiro, 2017)
Fil. Canepa, Juan F.. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina